Factors that influence the brand equity of Apple’s smartphone among students at Universiti Teknologi MARA Malacca City Campus / Nur Diana Ruslan and Nur Fatihah Ghafar - Ruslan, Nur Diana; Ghafar, Nur Fatihah (Faculty of Business and Management, 2016)
The purpose of this study is to study the factors that influence the brand equity of Apple’s smartphone among students at UiTM Malacca City Campus. This study conducted through distributing questionnaire to the students. The target population of this study was students at the UiTM Malacca City Campus and the sample size consist of 327 respondents. The study found significance strong positive correlation between brand equity and all the variables which is brand association, perceived quality, brand awareness and brand image. At the findings stated that among all of the factors, brand association has the greatest impact on influencing the brand equity on Apple’s smartphone. The study recommended that future research can be done towards other institutions or organizations for other factors that can influence on the Apple’s brand equity.